Glutamate Activity Regulates and Dendritic Development of J-RGCs - Elias, Eerik; Yang, Ning; Wang, Ping; Tian, Ning (Frontiers in Cellular Neuroscience, 2018)
Retinal ganglion cells (RGCs) have a wide variety of dendritic architectures, which are critical for their function specific synaptic circuitry formation. The developmental regulation of the dendrites of RGCs is thought to be subtype dependent. The purpose of this study was to characterize the dendritic development of a genetically identified RGC subtype, J-RGCs, and the roles of glutamate receptor activity on the dendritic development of these cells. We show that the dendrites of J-RGCs strictly ramified in the outer portion of the inner plexiform layer (IPL) of the retina at the age of postnatal day 8 (P8), mimicking the ramification pattern of adults. However, several other important features of dendrites underwent substantial developmental refinement after P8. From P8 to P13, the dendritic development of J-RGCs was characterized by a dramatic increase of dendritic length and the size of dendritic field. After eye opening, the dendritic development of J-RGCs was characterized by a tremendous decrease of the number of dendritic protrusions (spine-like structure) and a consolidation of the size of dendritic field. To determine whether the dendrite development of J-RGCs is regulated by glutamatergic activity, we conditionally knocked out the expression of obligatory subunit of NMDA receptors (NMDARs), NR1 (Grin1), in J-RGCs immediately after birth. We found that Grin1-/- J-RGCs have decreased dendrite outgrowth and dendritic field expansion but increased number of dendritic protrusion before eye opening. To determine if visual experience regulates the development of J-RGC dendrites, we raised the mice in complete darkness after birth. Light deprivation prevented the decrease of the number of dendritic protrusions and the consolidation of dendritic field of wild type mice after eye opening. However, cell-specific mutation of NMDARs prevented the effects of light deprivation on the dendrites of J-RGCs. Together, these results revealed the roles of light stimulation and NMDAR activity on the dendritic development of J-RGCs.